PLD.31 The rising rate of labour induction: what is causing the trend?. (9th June 2014) - Walker, S; van Rijn, BB; Macklon, NS; Howe, DT
Abstract : Background: The rate of induction of labour (IOL) in England is increasing 1 and has increased in Southampton by 31% in 10 years. Objectives: To evaluate whether trends in IOL are associated with maternal characteristics and/or changes in clinical practice. Method: Retrospective cohort study of 54, 727 singleton deliveries in Southampton after 24 weeks gestation between 2003 and 2012. Results: The IOL rate increased from 16.9 to 22.2%, while parity and mean gestational age at delivery remained constant. Mean body-mass index (BMI) increased significantly from 24.9 [95% CI 24.7–25.0] in 2003 to 25.8 [95%CI 25.7–26.0] in 2012 as did mean maternal age from 29.0 (95%CI 28.8–29.2) to 29.5 (95%CI 29.4–29.7). However, smoking rates decreased from 19.2 to 16.2%. Logistic regression analysis revealed that the likelihood of IOL was strongly associated with BMI (OR 1.04 [95%CI 1.04–1.05; p < 0.001]), age (1.01 [95% CI 1.00–1.01; p = 0.002]) and smoking (OR 0.92 [0.87–0.97]), which was also reflected in trends in IOL rates over time. In addition, we found that IOL rates for diabetes doubled from 3.2 to 6.5%. No changes were observed in the relative contribution of common indications, e.g. pre-eclampsia and post-term pregnancy. Discussion: The rising IOL rate is related to a rise in BMI in the pregnant population and corresponds to a rapid increase in the number of IOL for diabetes. The increasing prevalence of obesity and associated metabolic disorders among women of reproductive age, rather than more aggressive induction policies appears to underlie the increase in IOL rates. Reference: National Audit Office Report, 2013